The garden in the machine : planning and democracy in the Tennessee Valley Authority - Sachs, Avigail (Midcentury (Charlottesville, Va.), 2023)
"The book examines how regional planners, landscape architects, and architects working for the Tennessee Valley Authority advocated and designed for humane environments, in which people could interact with each other and with nature. The TVA project can be seen as a microcosm of how American architecture and landscape were transformed in the context of the Great Depression and World War II"--